Utilization of Augmented Reality as a Media Introduction to Pests in Rice Plants Using the Marker Base Method - Fatah Nur Saifullah; Enny Itje Sela (Kirana Publisher (KNPub), 2024)
Indonesia is an agrarian country where rice is a major commodity and a primary food source for the Indonesian population. To encourage the interest and knowledge of the younger generation as farmers, innovation is needed as a basic learning medium about agriculture, specifically rice. This research aims to develop a mobile application based on Marker-Based Augmented Reality (AR) to enhance the effectiveness of pest identification in rice plants. The application is designed to provide visual and interactive information to farmers about the types of pests that frequently attack rice plants, along with their characteristics. Data on rice pests are collected through literature reviews and interviews with several rice farmers. The application utilizes markers that can be recognized by the mobile device's camera to display 3D models and information about the pests. Testing results show that the application works well as expected, and the 3D object information regarding rice pests, along with their characteristics, can be displayed. Additionally, this application is expected to contribute to reducing crop losses due to pest attacks by improving farmers' quick and accurate responses, and it can serve as an effective and innovative tool in the field of agriculture, particularly in pest identification in rice plants.